1999
DOI: 10.1074/jbc.274.2.584
|View full text |Cite
|
Sign up to set email alerts
|

Endoglin Is an Accessory Protein That Interacts with the Signaling Receptor Complex of Multiple Members of the Transforming Growth Factor-β Superfamily

Abstract: Endoglin (CD105) is a transmembrane glycoprotein that binds transforming growth factor (TGF)-␤1 and -␤3, and coprecipitates with the Ser/Thr kinase signaling receptor complex by affinity labeling of endothelial and leukemic cells. The present study shows that in addition to TGF-␤1 and -␤3, endoglin interacts with activin-A, bone morphogenetic protein (BMP)-7, and BMP-2 but requires coexpression of the respective ligand binding kinase receptor for this association. Endoglin cannot bind ligands on its own and do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
411
1
12

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 530 publications
(441 citation statements)
references
References 77 publications
(84 reference statements)
14
411
1
12
Order By: Relevance
“…In addition, endoglin has been shown to interact with zyxin-related protein 1 resulting in a dramatic change in the structure of the actin cytoskeleton and the localization of zyxinrelated protein 1 (Sanz-Rodriguez et al, 2004). Second, in addition to TGF-b1, endoglin can bind, in association with different TGF-b superfamily receptors, to BMP2, BMP7, BMP9, activin A and TGF-b3 (Cheifetz et al, 1992;Barbara et al, 1999;Scharpfenecker et al, 2007), and has been reported to have a functional role in modulating responses to BMP2 (Ishibashi et al, 2010) and BMP7 (Scherner et al, 2007) in periodontal ligament cells and myoblasts, respectively. Although there are no published reports of endoglin modulating the response to other TGF-b family ligands in epithelial cells, it will be of interest in the future to determine whether the TGF-b1-independent functions of endoglin expressed on tumor cells may be mediated by binding to alternate ligands and/ or other TGF-b superfamily receptors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, endoglin has been shown to interact with zyxin-related protein 1 resulting in a dramatic change in the structure of the actin cytoskeleton and the localization of zyxinrelated protein 1 (Sanz-Rodriguez et al, 2004). Second, in addition to TGF-b1, endoglin can bind, in association with different TGF-b superfamily receptors, to BMP2, BMP7, BMP9, activin A and TGF-b3 (Cheifetz et al, 1992;Barbara et al, 1999;Scharpfenecker et al, 2007), and has been reported to have a functional role in modulating responses to BMP2 (Ishibashi et al, 2010) and BMP7 (Scherner et al, 2007) in periodontal ligament cells and myoblasts, respectively. Although there are no published reports of endoglin modulating the response to other TGF-b family ligands in epithelial cells, it will be of interest in the future to determine whether the TGF-b1-independent functions of endoglin expressed on tumor cells may be mediated by binding to alternate ligands and/ or other TGF-b superfamily receptors.…”
Section: Discussionmentioning
confidence: 99%
“…ENG has been shown to bind TGFb through interaction with other TGFb superfamily receptors (Barbara et al, 1999). Canonical TGFb signaling minimally involves a heteromeric complex involving type II (RII) and type I (RI) serine/threonine kinase receptors, resulting in RI activation, which in turn phosphorylates/activates Smad transcription factors (Shi and Massague, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, it may target specific ligand-receptor complexes analogous to endoglin (55) or betaglycan (56), or it may alter the balance between signaling through the canonical Smad pathway and other, non-canonical signaling pathways (25).…”
Section: Figmentioning
confidence: 99%